Edukasi Penggunaan Website Bagi Kelompok Sadar Wisata Panbo Beach - Helly Aroza Siregar; Febdwi Suryani; Pujiono Pujiono; Nurlasera Nurlasera (MENARA RIAU, 2023)
Panbo Beach is a natural tourist spot located in Batu Bersurat District, Kampar Regency, Riau Province. This tourist spot is a new tourist spot whose management is assisted by the Kelompok Sadar Wisata (Pokdarwis) Panbo Beach. The main problem faced by Panbo Beach is the small number of visitors. The purpose of implementing this Community service are to create a website to market this tourist spot, then provide training to operate the website. The method used in conducting this community service is, first, needs and design  system analysis, then carry out a workshop in purpose to using the website. The result of the community service were, the availability of a website with the address is http://panbobeach.com and increased knowledge and skills of workshop participants in operating the website.